2022
DOI: 10.21037/tcr-22-537
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of combined detection of CA72-4, CA19-9, and carcinoembryonic antigen comparing to CA72-4 alone in gastric cancer: a systematic review and meta-analysis

Abstract: Background Gastric cancer (GC) is one of the most common malignant tumors in humans. Carcinoembryonic antigen (CEA), carbohydrate antigen (CA) 19-9, and CA72-4 are all serum tumor markers for diagnosis of gastric cancer. However, the results of studies reporting the diagnosis of the combined three varied. In this study, the combined diagnostic performance of these 3 serum tumor markers was systematically evaluated. Methods PubMed, Embase, The Cochrane Library, China Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The diagnostic performance of carbohydrate antigen 72-4 (CA72-4), a mucin-like glycoprotein with a high molecular weight, is slightly superior to that of other conventional serological tumor markers for identifying gastric cancer 98 . A meta-analysis demonstrated that, among the single serological indicators for identifying gastric cancer, CA72-4 had the greatest diagnostic efficacy, with a sensitivity and specificity of 49% and 91%, respectively 99 . In the detection of progressive gastric cancer, the positivity rate of CA72-4 is almost double that of CA19-9 (37.5% versus 17.9%) 100 .…”
Section: Biomarker Screening For Early Gastric Cancermentioning
confidence: 99%
“…The diagnostic performance of carbohydrate antigen 72-4 (CA72-4), a mucin-like glycoprotein with a high molecular weight, is slightly superior to that of other conventional serological tumor markers for identifying gastric cancer 98 . A meta-analysis demonstrated that, among the single serological indicators for identifying gastric cancer, CA72-4 had the greatest diagnostic efficacy, with a sensitivity and specificity of 49% and 91%, respectively 99 . In the detection of progressive gastric cancer, the positivity rate of CA72-4 is almost double that of CA19-9 (37.5% versus 17.9%) 100 .…”
Section: Biomarker Screening For Early Gastric Cancermentioning
confidence: 99%
“…Overall, the most frequently used in clinical practice are the serum markers carcinoembryonic antigen (CEA), a glycoprotein, and carbohydrate antigen (CA)19-9, both found overexpressed in GC (193). However, these proteins, as well as other common markers such as alpha-fetoprotein, CA125 and CA72-4, lack sensitivity and sensibility, with the combined detection of CEA, CA19-9 and CA72-4 presenting greater diagnostic value (194)(195)(196). The most assessed biomarkers targeting earlier stages of gastric carcinogenesis, namely AG include serum pepsinogen (PG) levels, gastrin, and anti-H. pylori antibody detection (197).…”
Section: Liquid Biopsies As a Promising Source Of Dysbiosis-derived B...mentioning
confidence: 99%
“…Despite their prevalence, supported by 95% to 99% accuracy [2,16], these methods are hindered by time-consuming processes, high cost and a dependency on sophisticated instrumentation and skilled personnel [11,17]. Furthermore, protein biomarkers detected in such tests often lack adequate specificity [4] and sensitivity [18].…”
Section: Introductionmentioning
confidence: 99%